Taxes, Keiretsu Affiliation, and Income Shifting - Jeffrey D. Gramlich; Piman Limpaphayom; S. Ghon Rhee (Tinbergen Institute, 2002)
This paper provides evidence that keiretsu group member firms are subject to lowereffective tax rates than independent firms in Japan. As one explanation for this phenomenon, wedevelop a hypothesis that keiretsu firms strategically shift financially reported income amongaffiliates in order to reduce overall effective tax rates. Empirical evidence supports this income-shifting hypothesis since the positive relationship between pretax return m firm value and marginaltax rate status is significantly mitigated by keiretsu membership. Further, it appears that keiretsuincome shifting activities intensify when Japanese firms face economic recession, contrastingconjecture of weakening strength of keiretsu affiliation during this period. We also find evidencesupporting the view that benefactors of shifted income are compensated via increased dividends.
Keywords: G32; 330; Keyretsu; income shifting; marginal tax rate.; Konglomerat; Konglomerat; Unternehmensbesteuerung; Japan